Respuesta :
Answer:
0 = -24
Step-by-step explanation:
Distribute 18x-12
18x-12 = 18x-36
Then add 12 to both sides of the equation
18x-12+12 = 18x-36+12
Then add the numbers all together
18x+18x -24. The subtract 18x from both sides of the equation which means
18x= 18x- 24 turns into 18x-18x= 18x -24- 18x
combine both like terms and then your answer is 0 = -24
Given:
[tex]\to 18x - 12 = 3(6x - 12)[/tex]
To find:
find the number of solution=?
Solution:
[tex]\to 18x - 12 = 3(6x - 12)\\\\\to 18x - 12 = 18x -36\\\\\to 18x - 18x -12 +36=0\\\\\to 24=0[/tex]
Since x=0 so, there is no solution.
Learn more:
brainly.com/question/19930922